THE EFFECTS OF CERIUM PROMOTER ON THE PERFORMANCE OF COBALT-BASED CATALYSTS IN FISCHER TROPSCH SYNTHESIS FOR LIQUID FUEL PRODUCTION - Khalaf, Ahmed Lateef; Al-Zuhairi, Firas Khaleel; Kadhim, Wafaa Abdul; Rahim, Mohd Hasbi Ab (IIUM Engineering Journal, 2020)
An intensive work of Fischer-Tropsch synthesis (FTS) on a cobalt-based catalyst supported with cerium as a promoter was presented. The influence of space velocity and inlet gas feed ratio on FTS reaction performance was studied for the synthesized catalysts. Incipient wetness impregnation method was utilized to synthesis both unpromoted (25%Co/?-Al2O3) and cerium promoted (1%Ce-25%Co/?-Al2O3) catalysts. The proposed catalysts were examined by N2 adsorption and temperature-programed reduction (TPR). The performance of Ce-promoted and unpromoted cobalt-based catalysts in FTS was assessed in terms of activity and selectivity to desired products (C5+). The obtained results revealed that the addition of cerium by impregnation notably favours the reducibility of cobalt oxides by reducing the reduction temperature. In addition, the promoted catalysts exhibited higher activity and selectivity toward desired products at low space velocity and high inlet gas feed ratio as compared with the unpromoted catalysts. In conclusion, a cerium based cobalt catalyst considered as a suitable candidate to be used in gas to the liquid conversion process. ABSTRAK: Kajian intensif sintesis Fischer-Tropsch (FTS) adalah tentang pemangkin berasas kobalt bersama penggalak cerium. Pengaruh tindak balas FTS pada halaju ruang dan nisbah suapan gas masuk dikaji menggunakan pemangkin yang disintesis. Kaedah impregnasi insipien basah telah digunakan bagi mensintesis pemangkin bukan penggalak (25%Co/?-Al2O3) dan penggalak cerium (1%Ce-25%Co/?-Al2O3). Pemangkin ini diuji dengan penjerapan N2 dan pengurangan suhu terprogram (TPR). Hasil tindak balas penggalak-Ce dan bukan penggalak berasas kobalt dalam FTS diperiksa dari segi aktiviti dan pemilihan hasil (C5+). Tindak balas menunjukkan dengan penambahan cerium melalui kaedah impregnasi dengan ketara mengurangkan kobalt oksida bersama pengurangan suhu. Di samping itu, pemangkin penggalak menunjukkan aktiviti dan pemilihan ke arah hasil pada halaju ruang dan nisbah suapan gas masuk yang tinggi berbanding dengan pemangkin bukan penggalak. Kesimpulan, pemangkin kobalt berasas cerium dianggap sesuai sebagai pemangkin sintesis bagi digunakan dalam proses penukaran gas ke cecair.